The use of therapeutic plasmapheresis in preventive and sports medicine - Gilmutdinova, Ilmira; Kudryashova, Irina; Kostromina, Elena; Yafarova, Inessa; Gilmutdinov, Rinat; Kaverina, Irina; Isaev, Andrey; Moskalev, Alexey (BIO web of conferences, 2022)
Maintenance of active longevity, preservation of physical activity, and prevention of decreased mobility associated with injury or age of patients are among the most urgent tasks for modern healthcare. The suppression of pathological processes and activation of defense systems at the cellular and organismal levels are the main routes for solving these problems. Several initial anti-aging therapy approaches are detoxification, rheocorrection, and immunocorrection. In these areas, methods of extracorporeal hemocorrection, in particular, therapeutic plasmapheresis, are effective. This study aimed to evaluate the effectiveness of hardware plasmapheresis with albumin compensation by assessing the dynamics of circulating age-related biomarker levels in randomly selected patients. Twenty human subjects of both sexes aged 40–55 years with an increase in one or more aging-related biomarkers participated in this study. The patients were randomly divided into two groups with ten people each. Patients from Group 1 underwent therapeutic plasmapheresis with albumin replacement (four procedures with a 2-day interval). Patients from Group 2 were offered plasmapheresis treatment with saline replacement. The levels of aging-related biomarkers were determined in the blood of patients before and 30 days after starting treatment. Preliminary data showed that plasmapheresis with albumin replacement in randomly selected male and female patients was accompanied by normalization of the selected aging biomarkers. Thirty days after the start of the plasmapheresis treatment, a decrease in both biological and phenotypic age was determined. Further studies are needed to investigate the effects of nutritional factors on aging biomarkers with and without plasmapheresis treatment. Based on the obtained results, recommendations will be made on the use of plasmapheresis in preventive and sports medicine. The use of this method will help reduce the biological age of patients and, as a result, reduce the risks of developing age-related diseases and disabilities and contribute to prolonging life and improving its quality.